Digital Humanities e moda - Rossi, Valentina (ZoneModa Journal, 2020)
To answer the question posed by the call: Could the pandemic, the pervasive use of the Web and the experimentation of Extended Reality technologies give a boost to fashion archives? it is necessary to undertake a analysis of different case studies that over the years have been confronted with Digital Humanities practices.The essay aims to outline a methodological lecture on museum and archival practices related to digital humanities. Since March 2020, museums and archives have accelerated the data restitution process and reinterpreted the functions of institutions through digital practices and virtual exhibitions - that do not aspire to replace the real ones - and demonstrating how these are placed on a different level of reading. They can certainly integrate with the museum and physical itinerary, but they can also take place independently of it. The debate on Digital Humanities and Virtual Exhibitions is now wide and articulated and one of its major authors, Jeffrey Schnapp, writes of Knowledge design: we find ourselves creating new forms of knowledge assuming the current conditions that contemporaneity offers us, while other critical perspectives are aimed at restoring the difference on the role of the document as such or on the method of construction and the impact of digital platforms